Portal Wissen = Departure - Zimmermann, Matthias; Mikulla, Stefanie (Dr.); Kampe, Heike; Horn-Conrad, Antje; Lass, Sander (Dr.) (2021)
On October 20, 1911, the Norwegian Roald Amundsen left the safe base camp “Framheim” at the Bay of Whales together with four other explorers and 52 sledge dogs to be the first person to reach the South Pole. Ahead of them lay the perpetual ice at temperatures of 20 to 30 degrees Celsius below zero and a distance of 1,400 kilometers. After eight weeks, the group reached its destination on December 13. The men planted the Norwegian flag in the lonely snow and shortly afterwards set off to make their way back – celebrated, honored as conquerors of the South Pole and laden with information and knowledge from the world of Antarctica. The voyage of Amundsen and his companions is undoubtedly so extraordinary because the five proved that it was possible and were the first to succeed. It is, however, also a symbol of what enables humans to push the boundaries of their world: the urge to set out into the unknown, to discover what has not yet been found, explored, and described. What distinguishes science - even before each discovery and new knowledge – is the element of departure. Questioning apparent certainties, taking a critical look at outdated knowledge, and breaking down encrusted thought patterns is the starting point of exploratory curiosity. And to set out from there for new knowledge is the essence of scientific activities – neither protected nor supported by the reliable and known. Probing, trying, courageously questioning, and sensing that the solid ground, which still lies hidden, can only be reached again in this way. “Research is always a departure for new shoreless waters,” said chemist Prof. Dr. Hans-Jürgen Quadbeck-Seeger. Leaving behind the safe harbor, trusting that new shores are waiting and can be reached is the impetus that makes science so important and valuable. For the current issue of the University of Potsdam’s research magazine, we looked over the shoulders of some researchers as they set out on new research journeys – whether in the lab, in the library, in space, or in the mind. ...